A brown tumor secondary to hyperparathyroidism in the maxilla, skull, scapula, and femora. Issue 1 (2nd January 2021) - Psaila, Alison; Conti, Luca; Azzopardi, Alexander P.; Coppini, David V.
Abstract: Primary hyperparathyroidism presenting with diffuse skeletal involvement, such as discrete osteoclastic bone lesions, is rare. We describe a 35-year-old woman who presented with a left mandibular mass that rapidly enlarged over 3 weeks. Radiological, histological, and biochemical investigations led to the diagnosis of brown tumor secondary to primary hyperparathyroidism. A neck ultrasound revealed a 1.5 × 2.3 × 4.6 cm mass at the lower pole of the left thyroid lobe, suggestive of a parathyroid adenoma. Bone scan showed additional abnormal foci of increased uptake in the maxilla, both femora, skull, and scapula. Brown tumors are treated primarily by correcting the underlying endocrine disorder, and a parathyroidectomy was performed.